Effectiveness of Rosella Flower Extract Addition (Hibiscus sabdariffa L.) on the Physicochemical Quality of Liquid Soap - Yardani, Jesi; Ulimaz, Almira; Awalina, Rahmi; Linangsari, Titis (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2023)
Soap is one of the daily necessities that is often used, from household scale to industrial scale. Soap serves to kill germs so that the skin surface becomes clean. Therefore, soap usually contains Triclocarban which functions as an antibacterial agent. However, this substance can cause bacterial resistance to antibiotics if used for a long period of time. Therefore, it is necessary to substitute this chemical substance which is more natural such as red Rosella plant flower extract (Hibiscus sabdariffa L.). The purpose of this study was to analyze the effectiveness of the addition of Rosella flower extract on the physicochemical quality of liquid soap. The research method is experimental laboratory. The formulations of red Rosella flower extract used were 0%, 0.5%, 1%, 1.5%, and 2%. Soap was tested for physical characteristics, namely color and aroma, while testing chemical characteristics with a pH test. Data analysis was carried out descriptively qualitative. The results showed that the addition of Rosella flower extract proved effective in changing the physical characteristics of soap, namely odor and color. The higher the percentage of red Rosella flower extract formulation added, the more red-colored the soap and the more the soap has a distinctive Rosella flower aroma. The higher the percentage of red Rosella flower extract formulation added, the pH of the soap is closer to neutral. Soap with a pH that tends to neutral pH is better for the skin because it does not damage the lipid layer of the skin surface. Based on the results of this study, it can be concluded that red Rosella flower extract (Hibiscus sabdariffa L.) is proven to effectively improve the physicochemical quality of liquid soap